Decay rate of the excited surface electron states on liquid helium - Monarkha, Yu.P.; Sokolov, S.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The low temperature bound of the decay rate of the excited surface electron states on liquid helium is theoretically studied. It is shown that the lifetime and dephasing time of the surface electron states are strongly limited by spontaneous emission of couples of short-wavelength capillary wave quanta (ripplons). These two-ripplon scattering processes are of the second order in the nonlinear interaction Hamiltonian. In contrast to the usual one-ripplon scattering contribution, the decay rate found here cannot be substantially reduced neither by lowering temperature nor by external magnetic field, which is important for recently discussed implementation of quantum bits in such a system.